2007
DOI: 10.1146/annurev.psych.58.110405.085641
|View full text |Cite
|
Sign up to set email alerts
|

Ostracism

Abstract: In this review, I examine the social psychological research on ostracism, social exclusion, and rejection. Being ignored, excluded, and/or rejected signals a threat for which reflexive detection in the form of pain and distress is adaptive for survival. Brief ostracism episodes result in sadness and anger and threaten fundamental needs. Individuals then act to fortify or replenish their thwarted need or needs. Behavioral consequences appear to be split into two general categories: attempts to fortify relationa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

75
1,697
12
95

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 1,630 publications
(1,879 citation statements)
references
References 86 publications
75
1,697
12
95
Order By: Relevance
“…When social exclusion is detected, even the most subtle cue of exclusion, it activates the neural circuitry of physical pain (e.g., Eisenberger, Lieberman, & Williams, 2003) and elicits emotional distress (e.g., Williams, Cheung, & Choi, 2000). Immediate social exclusion is extremely aversive (Williams, 2007) and longer lasting exclusion may have serious ill effects, including feelings of helplessness, alienation, and despair, and often leads to antisocial behavior such as direct and indirect aggression toward and derogation of the person doing the exclusion (e.g., Twenge, Baumeister, Tice, & Stucke, 2001). Recently, Kerr and Levine (2008) suggested that even signs of anticipated exclusion and avoidance (e.g., not approaching, moving or turning away, not saying hello) are reliably associated with feelings of rejection and exclusion.…”
Section: The Perception Of Concealment As a Signal Of Exclusionmentioning
confidence: 99%
“…When social exclusion is detected, even the most subtle cue of exclusion, it activates the neural circuitry of physical pain (e.g., Eisenberger, Lieberman, & Williams, 2003) and elicits emotional distress (e.g., Williams, Cheung, & Choi, 2000). Immediate social exclusion is extremely aversive (Williams, 2007) and longer lasting exclusion may have serious ill effects, including feelings of helplessness, alienation, and despair, and often leads to antisocial behavior such as direct and indirect aggression toward and derogation of the person doing the exclusion (e.g., Twenge, Baumeister, Tice, & Stucke, 2001). Recently, Kerr and Levine (2008) suggested that even signs of anticipated exclusion and avoidance (e.g., not approaching, moving or turning away, not saying hello) are reliably associated with feelings of rejection and exclusion.…”
Section: The Perception Of Concealment As a Signal Of Exclusionmentioning
confidence: 99%
“…De acordo com Williams (2007), o termo pode ser compreendido como um processo de respostas às frustações das necessidades relativas à autoestima e ao sentimento de pertencimento na sociedade.…”
Section: O Ostracismo Socialunclassified
“…A exclusão social frustra essa necessidade e pode ocasionar efeitos psicológicos que afetam a saúde do indivíduo (Williams, Zadro, 2005;Williams, 2007;Bastian, Haslam, 2010;Hawkley, Williams, Cacioppo, 2011).…”
Section: O Ostracismo Socialunclassified
See 2 more Smart Citations